Rapid hardening process for starch-based powder bed 3D printing. (March 2022) - Cheng, Ting-Yu; Liao, Ying-Chih
Abstract: In this study, a microwave-assisted crosslinking process was developed to rapidly harden printed objects from binder jet 3D printers. A starch-based powder formula was first developed to pave smooth layers in the powder bed. An aqueous crosslinking agent (glutaraldehyde) was printed over the paved layers to form three-dimensional objects with a layer-by-layer strategy. After the 3D printing process, the printed three-dimensional samples were heated with a microwave oven and can be hardened within 70 s to trigger the endothermic crosslinking reaction between the starch powder and glutaraldehyde. The high mechanical strength of crosslinked starch after microwave heating provided 3D printed objects with a high flexural strength up to 32 MPa. Several examples were also demonstrated to show the versatility of this method in producing rigid structures with high mechanical strength for fast prototyping applications. Graphical abstract: Unlabelled Image Highlights: A microwave heating method is developed to finish starch-based 3D printing post-treatment in 70 s. Food-graded starch, maltodextrin, and cellulose are used as materials without polymeric resin infiltrant. The starch can be rapid hydrated and gelatinized with the existence of water by using microwave oven heating. Glutaraldegyde crosslinking further improves the starch bonding strength and enhance the flexural strength to 32 MPa. Microwaved post-treated 3D object shows great size accuracy and mechanical strength.